Factors associated with adherence to anti-hypertensive medication among patients attending a secondary referral hospital, in Kirinyaga county, Kenya - Muchiga, Beatrice; Lakati, Alice; Ndege, Samson (International Journal Of Community Medicine And Public Health, 2025)
Background: In Kenya, hypertension is rising, but adherence levels are poorly documented. The purpose of this study was to assess the level of adherence to antihypertensive medication and identify the patient- and health system-related factors influencing adherence among hypertensive patients in Kirinyaga County. Methods: This descriptive cross-sectional study assessed medication adherence among 237 hypertensive patients aged 18–60 years at Kerugoya County Referral Hospital between October and December 2024. Systematic sampling was used. Data was collected using a structured questionnaire incorporating the MMAS-8 and analyzed using SPSS with descriptive and inferential statistics. Results: Slightly more than a third of patients did not take their hypertension medication as prescribed. 39% (n=93) lacked health insurance and married individuals were more likely to adhere than the unmarried, while higher hospital fees were linked to non-adherence. Two-thirds had comorbidities and patients with diabetes (89%, n=82), those who monitored their blood pressure at home (91%, n=136) and those aware that skipping medication worsens hypertension (89%, n=133) showed better adherence. Resources and education were generally available. Longer doctor waits times discouraged adherence. Adherent patients were 6 times more likely to report no side effects (OR = 6.058) and more likely to spend less time at the pharmacy (OR=0.977). Conclusions: This study recommends strengthening health education on adherence, especially regarding home blood pressure monitoring and the risks of missed doses. The facilities should reduce waiting times, sensitize on NHIF enrollment. Further research is necessary to explore the role of social support in promoting adherence.